Modèle psycho-social et impensé numérique dans l'élaboration d'un dispositif pédagogique - Aude Seurrat (Centre National d'Enseignement à Distance, 2018)
The paper proposes a review of an experience of participating in a Council of Europe project and aims to highlight the different issues that have been raised during the adaptation of this tool, focused on intercultural relations, on a tool focused on intercultural encounters mediated by digital media. This article will allow us to show in more detail how the psycho-social model of interpersonal relations is limited for understanding the specificities of distance communication.